SPECTACLE SOCIETY SITUASIONISME GUY DEBORD: TEORI DAN PRAKTIK - Wijanarko, Rio; Nugroho, Wahyu Budi; Krisna Aditya, I.G.N. Agung (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This research aims to examine the concept, contextualization, and relevance of Guy Debord’s thought. The method used in this research is qualitative-exploratory with a bibliographic research type. The results of this research describe human alienation since the 20th century at its culmination. All moments of modern human life have rests on the logic of commodities. The practice of commodification here has to go through a process of spectacularization that requires additional fantasies for each commodity. In addition, this research found that the détournement method was manifested through the emergence of the art of shitposting. It is proven in this research that the fictional character Nurhadi-Aldo and the fictional comic Udayanagakure have emancipatory power and are able to catalyze changes in mindset—just like the pixel girl Miquela on Instagram. Keywords: spectacle society, situationism, Guy Debord, influencer, détournement